2000
DOI: 10.1046/j.1365-2249.2000.01381.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood fetal microchimerism in primary biliary cirrhosis

Abstract: SUMMARYThe autoimmune nature of primary biliary cirrhosis (PBC) is well established. We tested the hypothesis that fetal microchimerism indicated by the persistence of circulating fetal cells in women years after pregnancy might contribute to the aetiopathogenesis of PBC through a graft-versus-host-like response. We extracted DNA from the peripheral blood cells of 36 women carefully selected from 173 consecutive PBC patients, who were matched with 36 healthy women by age, age of last son, and number of childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 23 publications
0
34
1
2
Order By: Relevance
“…Fanning et al 89 demonstrated that detectable fetal DNA in liver samples years after pregnancy was associated with PBC, while other groups failed to recapitulate the hypothesis. 90,91 The hypothesis, mostly based on data in other conditions, still awaits definitive confirmation or denial.…”
Section: Mhc and Pbcmentioning
confidence: 99%
“…Fanning et al 89 demonstrated that detectable fetal DNA in liver samples years after pregnancy was associated with PBC, while other groups failed to recapitulate the hypothesis. 90,91 The hypothesis, mostly based on data in other conditions, still awaits definitive confirmation or denial.…”
Section: Mhc and Pbcmentioning
confidence: 99%
“…Two other studies found no significant difference in DNA extracted from whole blood (23) or from PBMC and liver biopsy specimens (24) in patients with primary biliary cirrhosis compared with controls. In situ hybridization (ISH) was used to examine liver biopsy specimens for cells with a Y-chromosome signal in a small study; no Y chromosome-containing cells "within inflammatory cell infiltrates" were detected in 10 women with primary biliary cirrhosis, 5 of whom had sons (25).…”
Section: Fetal Microchimerism In Other Autoimmune Diseasesmentioning
confidence: 91%
“…Primary biliary cirrhosis strongly resembles chronic GVHD of the liver. Five studies have examined fetal microchimerism in this condition (22)(23)(24)(25)(26). The initial study used a quantitative assay to test DNA extracted from liver biopsy specimens (22).…”
Section: Fetal Microchimerism In Other Autoimmune Diseasesmentioning
confidence: 99%
“…This phenomenon of fetal-maternal chimerism has been studied in PBC but no strong evidence for a significant involvement with disease has been found (87,(88)(89)(90). However, microchimerism could be a significant factor on the etiology of PBC for a subset of individuals, likely in concert with further genetically encoded autoimmune propensity, and therefore should not be so quickly discounted.…”
Section: The Sex Chromosomes and Pbcmentioning
confidence: 99%